Aplikasi Focus Tosm Sebagai Salah Satu Instrumen Matematika Detik Berbasis Android - Ariela Estiana; Anggraini Mulwinda (Fakultas Teknik Universitas Negeri Malang, 2019)
This research aimed to find the students focus level that was taken from the second mathematic manual instrument and was applied in the Android platform to facilitate the usage and could be accessed by anyone and anywhere. This research used the waterfall method in communication, planning, application modelling, coding, testing, and marketing stages. The results showed that the Android-based Focus ToSM was in an adequate category based on the conducted tests. The tests, among others, were material expert validation test that obtained 86.67 percent, media expert validation test with the result of 90.83 percent, and application implementation that got 90.33 percent that was conducted in Public Junior High School 1 Slawi from 30 students as the sample.